The Effect of Jackfruit Seed (Artocarpus heterophyllus Lamk) and Mung Bean (Vigna radiata) Composite Flour Fortification on Protein Content and Acceptability of Crackers - Paramita, Ni Wayan Nadia; Widnyani, Ida Ayu Putu Ary; Rabani RS, I Gusti Agung Yogi; Sintyadewi, Putu Rima; Putra, Anak Agung Ngurah Dwi Ariesta Wijaya (Jurnal Pijar Mipa, 2025)
Adequate balance of nutrient intake is crucial due to its biological functions in supporting growth and muscle formation, particularly protein. Jackfruit seeds and mung beans are high-protein raw materials with potential for incorporation into protein-enriched foods, such as crackers. The purpose of this study was to determine the effect of jackfruit seed–mung bean composite flour fortification on protein content and sensory acceptability, and to identify the optimal fortification ratio in crackers. This experimental study employed a Completely Randomized Design (CRD) with five treatments representing different wheat-to-composite flour ratios. Data were analyzed using one‐way ANOVA to test for significant differences, followed by Duncan’s multiple range test to identify the best treatment. Findings indicated that the highest protein content (11.13 %) was achieved in treatment P5 (50 % wheat flour: 50% composite flour). Panellists rated color at 3.93 (like), aroma at 3.56 (like), texture at 3.86 (like), taste at 3.63 (like), and overall acceptability at 3.70 (like). The optimal fortification ratio was identified as P2 (80 % wheat flour: 20% composite flour). Fortification of crackers with jackfruit seed–mung bean composite flour enhances protein content and maintains favorable sensory attributes, with an 80:20 wheat-to composite flour ratio yielding the best overall results.